Волинські міста у сфері діяльності маршалка Волинської землі та ключника (середина XV - 60-ті рр. XVI ст.) - Бортнікова, Алла; Bortnikova, Alla (Східноєвропейський національний університет імені Лесі Українки, 2014)
Досліджено діяльність, статус і повноваження урядників Великого князівства Литовського – маршалка Волинської землі та ключника в містах краю від середини ХV до 60-х рр. ХVІ ст.

The article analyzes the experience of interaction Uryadov Marshal Volhyn and kluchnik with the cities of Volyn. Explores the history of the establishment of posts Marshal Volhyn and kluchnik. Defined personal structure of the constable, the scope of their authority, responsibilities. Marshal Volhyn led hierarchy of local officials. His powers were in the implementation of management functions primarily local armed forces. In Volyn Uryadov Marshal joined with Uryadov Lutsk and Vladimir elders. The rich and powerful landowners held this position. Klyuchnik and his Uryadov who often joined with the mayor and Uryadov mostovnichego, remained subordinate chiefs Volhyn. Klyuchnik dealt with problems of land use, to keep order in the city, to monitor the implementation of trade rules, and others. It is shown kluchnik interaction with the cities of Volhynia in particular to guide the construction and repair of locks, bridges and ferries.
Volhyn Cities in the Marshal Activities of the Volhyn Lands and Kluchnik (XV -– 60th. XVI century)
Keywords: Велике князівство Литовське; Волинь; місто; привілей; маршалок; ключник; староста; Grand Duchy of Lithuania; the Polish Crown; Volhynia land; Privilege; marshal; steward.